A study of individuality of diaspora chitra banerjee divakaruni's identity and nationality (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Diaspora experiences are accurately portrayed through their representation and expression, which place an emphasis on culture, custom, history, heritage, and other related topics. It's also worth noting that women from the Diaspora have contributed to a wide range of literary genres, from fiction and poetry to memoir and nonfiction. The writers of the Diaspora have established themselves as masters of the genre of fiction. Though excellent poets and short story writers from the Indian diaspora have emerged in recent years. The scope of this theory, however, is limited to novels. There are two motivations behind this restriction: First, contemporary women writers of South Asian descent who have published widely and won critical acclaim. The literary form used to create these stories that empower Diaspora subjectivities is also examined in the thesis, as how it intersects with female sensibilities. However, due to the fact that this type of literature has only flourished in the previous two decades, only works published after 1998 are chosen for close examination. There are a lot of factors at play here, but its sheer size is the most obvious one. It has been noted that the South Asian Diaspora today boasts a larger number of women writers working in English than at any time in the past. It has been shown that female authors, in addition to having a larger representation of female authors, also have a greater sensitivity to Diaspora issues than male authors. There has been work done to demonstrate how this literature sheds light on the predicament of the Diasporic subject who exists on the cultural periphery. These authors, whether they are first- or second-generation Diasporas, infuse their writing with a Diaspora sensibility.